CARACTERISATION CARDIORESPIRATOIRE ET METABOLIQUE DE L’ADAPTATION A L’EFFORT CHEZ LE JEUNE NAGEUR - Benkara, Yassine; Benlabed, Abderrahim; Chih, Fouad; Himoud, Ahmed; Sellami, Abderrahim (Journal of Human Sciences, 2018)
This work aims morphofunctional adaptations of young swimmers, children and teenagers, exercise and training. 28 swimmers divided into 4 stages according to Tanner staging. (Age: 12.85 ± 2.30 years, height 159.02 ± 14.5 cm, weight: 51.05 ± 13.86 kg) were assessed twice, at the beginning and the end of the sports season. The investigations concerned the assessment of VO2max, the change in heart rate, anthropometric measurements and blood samples. Also, an analysis has been devoted to the parameters of the training load. The muscular effort test was performed according to the protocol of Wasserman (1986). In our study, we recommend the age established between the 3rd and 4th stage of puberty according to Tanner staging for the increase of the loads of training without striking a blow at the health of these athletes.